Urbana kulturna politika in urbana regeneracija na primeru Maribora, Nove Gorice in Ljubljane - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
The importance of urban cultural policy and investments in cultural infrastructure for urban regeneration and revitalization is presented in the paper. In the first part of the paper the theoretical framework of culture led urban regeneration is presented. The importance of concept of creative city for economic urban regeneration is highlighted. In the central part of the paper the author presents the general overview, analysis and evaluation of the goals and measures of urban cultural policy as a mean for urban regeneration in selected Slovene cities Maribor, Nova Gorica and Ljubljana. Based on analysis of strategic development documents and policies and finished investments in cultural infrastructure an impact on urban regeneration and revitalization of selected urban areas is evaluated. In all selected cities culture is recognized as an essential tool for urban regeneration. Main anticipated effects of investments in cultural infrastructure are revitalization of derelict urban areas, development of cultural tourism, better image of the city and improved quality of life for residents.
Keywords: cultural infrastructure; culture; kultura; kulturna infrastruktura; Ljubljana; Maribor; Nova Gorica; prostorsko planiranje; Slovenia; Slovenija; spatial planing; urban cultural policy; urban geography; urban regeneration; urban revitalisation; urbana geografija; urbana kulturna politika; urbana regeneracija; urbana revitalizacija